A de novo X;8 translocation creates a PTK2-THOC2 gene fusion with THOC2 expression knockdown in a patient with psychomotor retardation and congenital cerebellar hypoplasia. Issue 8 (7th June 2013) - Di Gregorio, Eleonora; Bianchi, Federico T; Schiavi, Alfonso; Chiotto, Alessandra M A; Rolando, Marco; Verdun di Cantogno, Ludovica; Grosso, Enrico; Cavalieri, Simona; Calcia, Alessandro; Lacerenza, Daniela; Zuffardi, Orsetta; Retta, Saverio Francesco; et al.
Abstract : Background and aim: We identified a balanced de novo translocation involving chromosomes Xq25 and 8q24 in an eight year-old girl with a non-progressive form of congenital ataxia, cognitive impairment and cerebellar hypoplasia. Methods and Results: Breakpoint definition showed that the promoter of the Protein Tyrosine Kinase 2 ( PTK2, also known as Focal Adhesion Kinase, FAK ) gene on chromosome 8q24.3 is translocated 2 kb upstream of the THO complex subunit 2 ( THOC2 ) gene on chromosome Xq25. PTK2 is a well-known non-receptor tyrosine kinase whereas THOC2 encodes a component of the evolutionarily conserved multiprotein THO complex, involved in mRNA export from nucleus. The translocation generated a sterile fusion transcript under the control of the PTK2 promoter, affecting expression of both PTK2 and THOC2 genes. PTK2 is involved in cell adhesion and, in neurons, plays a role in axonal guidance, and neurite growth and attraction. However, PTK2 haploinsufficiency alone is unlikely to be associated with human disease. Therefore, we studied the role of THOC2 in the CNS using three models: 1) THOC2 ortholog knockout in C.elegans which produced functional defects in specific sensory neurons; 2) Thoc2 knockdown in primary rat hippocampal neurons which increased neurite extension; 3) Thoc2 knockdown in neuronal stem cells (LC1) which increased their in vitro growth rate without modifying apoptosis levels. Conclusion: We suggest that THOC2 can play specific roles in neuronal cells and, possibly in combination with PTK2 reduction, may affect normal neural network formation, leading to cognitive impairment and cerebellar congenital hypoplasia.